BUILDING PUBLIC TRUST: GOVERNMENT COMMUNICATION IN THE IMPLEMENTATION OF SOCIAL WELFARE POLICIES - Pratiwi , Endah (PT Altin Riset Publishing, 2025)
Public trust is one of the most fundamental elements in the successful implementation of government policies, especially those related to improving public welfare. In the context of public communication, the government plays an important role as the main source of information, opinion maker, and manager of public perception of the policies being implemented. This article aims to analyse how government communication strategies play a role in building, maintaining, and strengthening public trust in the process of implementing public welfare policies. This study adopts a qualitative approach with a descriptive paradigm, conducted through a literature review as the basis for analysis, which includes an analysis of various official government documents, academic publications, policy reports, and media reports. The results of the study show that public trust can be fostered through communication that is transparent, participatory, consistent, and empathetic. In addition, active community involvement in the process of policy formulation and evaluation has been proven to increase public legitimacy and support for government programmes. Thus, effective public communication is not only a channel for conveying information, but also a strategic instrument in strengthening the credibility, accountability, and positive image of the government in the eyes of the community.